2020
DOI: 10.1038/s41467-020-17799-w
|View full text |Cite
|
Sign up to set email alerts
|

Transient dormant monomer states for supramolecular polymers with low dispersity

Abstract: Temporally controlled cooperative and living supramolecular polymerization by the buffered release of monomers has been recently introduced as an important concept towards obtaining monodisperse and multicomponent self-assembled materials. In synthetic, dynamic supramolecular polymers, this requires efficient design strategies for the dormant, inactive states of the monomers to kinetically retard the otherwise spontaneous nucleation process. However, a generalized design principle for the dormant monomer state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…The work presented here represents a proof of conceptwe have demonstrated that it is possible to couple molecular-level processes, such as replication processes, with the formation of a supramolecular material. The spacer utilized in this system is essentially inert and is used simply for its rigid molecular framework.…”
Section: Discussionmentioning
confidence: 99%
“…The work presented here represents a proof of conceptwe have demonstrated that it is possible to couple molecular-level processes, such as replication processes, with the formation of a supramolecular material. The spacer utilized in this system is essentially inert and is used simply for its rigid molecular framework.…”
Section: Discussionmentioning
confidence: 99%
“…[253][254][255] Redox control using Na 2 S 2 O 4 /O 2 256 over the folding of a NDI-pyrene donor-acceptor complex was also exploited for making supramolecular polymers with low dispersity. 257 Here also, the combination of supramolecular and dynamic covalent chemistries is rich in discoveries. The George group recently reported dissipative systems derived from their dormant charge-transfer monomer which turns into an activated amphiphile upon imine formation.…”
Section: Transient Supramolecular Polymersmentioning
confidence: 99%
“… 256 ) over the folding of a NDI-pyrene donor–acceptor complex was also exploited for making supramolecular polymers with low dispersity. 257 …”
Section: Recent Developmentsmentioning
confidence: 99%
“…Halogens play a crucial role in complex biological processes, such as ligand binding or molecular folding. Oftentimes, these events are facilitated by directional secondary interactions, where the halogen acts either as an electron acceptor unit (i.e., halogen bonding) or as a Lewis-basic hydrogen bond acceptor. In addition to natural systems, halogens are common structural elements of numerous organic and inorganic compounds, conferring them unique physicochemical properties. , For example, the relevance of halogens in synthetic materials (e.g., polyfluorinated coatings, , polybrominated flame-retardants , ), pharmaceuticals, , pesticides, and other applications (e.g., catalysis) has been widely documented. Additionally, halogens are well-known supramolecular synthons that have been used in different fields, such as anion binding, gels, , liquid crystals, , crystal engineering, and others. , More specifically, supramolecular polymers have recently been recognized as important 1D/2D model systems that can shed light on various aspects of far more complex 3D crystallization processes. This is due to the fact that their dynamic self-assembly into different molecular packings is strongly influenced by kinetic effects. Nevertheless, in the field of supramolecular polymerization, halogen effects remain poorly understood, and investigations have been restricted to halogen bonding or the effect of polyfluorinated side groups. …”
Section: Introductionmentioning
confidence: 99%